2017
DOI: 10.1155/2017/7985728
|View full text |Cite
|
Sign up to set email alerts
|

Protein Intake, Especially Vegetable Protein Intake, Is Associated with Higher Skeletal Muscle Mass in Elderly Patients with Type 2 Diabetes

Abstract: Background/Aims Protein intake is important for maintaining muscle mass in general population. However, it remains to be elucidated the association between dietary protein intake and skeletal muscle mass in elderly patients with type 2 diabetes. Methods In this cross-sectional study of 168 elderly patients with type 2 diabetes, we investigated the relationship between skeletal muscle index (SMI) and protein intake. Bioimpedance analysis was used for measurement for skeletal muscle mass (kg) and SMI (%), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
2
23
1
1
Order By: Relevance
“…Another study revealed that protein intake was important for the maintenance of muscle mass in elderly people . In a previous study, we also reported that protein intake is associated with muscle mass . A protein intake of 1 to 1.2 g/kg BW per day is generally recommended for the maintenance of muscle mass in the elderly .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Another study revealed that protein intake was important for the maintenance of muscle mass in elderly people . In a previous study, we also reported that protein intake is associated with muscle mass . A protein intake of 1 to 1.2 g/kg BW per day is generally recommended for the maintenance of muscle mass in the elderly .…”
Section: Discussionmentioning
confidence: 77%
“…It has been estimated that healthy elderly people should consume 1 g protein per kilogram of body weight each day to promote muscle protein anabolism and increase muscle mass . In addition, we recently demonstrated that protein intake is significantly associated with skeletal muscle mass in elderly patients with T2D . However, it is possible that the mechanisms underlying sarcopenia differ between a diabetic aging population and a healthy aging population because of autophagy, muscle protein degradation, and mitochondrial dysfunction caused by insulin resistance …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cross‐sectional study, we used the patients’ data, which were gathered to clarify the impact of sarcopenia on the natural history of patients with diabetes from December 2016 to December 2017. The inclusion criteria of this cross‐sectional study were older patients with type 2 diabetes (aged ≥65 years) without physical inactivity, who agreed to participate in the KAMOGAWA‐DM cohort study . We excluded patients who were not tested with a multifrequency impedance body composition analyzer and patients without data for handgrip strength, and without four or more blood pressure readings for 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria of this cross-sectional study were older patients with type 2 diabetes (aged ≥65 years) without physical inactivity, who agreed to participate in the KAMOGAWA-DM cohort study. 14 We excluded patients who were not tested with a multifrequency impedance body composition analyzer and patients without data for handgrip strength, and without four or more blood pressure readings for 1 year. None of the patients changed medication for hypertension during the 1 year of this study.…”
Section: Study Patientsmentioning
confidence: 99%